Flora roślin naczyniowych rezerwatu „Jamno” - Pawicka, Katarzyna; Woziwoda, Beata; Wolski, Grzegorz J. (Biuletyn Szadkowski, 2012)
The 96 vascular plant species belonging to 36 families have been identified in "Jamno" nature reserve during field investigations which were done in 2011. The species repre sent different types of growth (= life forms in Raunkiaer's classification system), with hemicryptophytes being the dominant form. The flora contains plants from various eco logical groups depending on light requirements, moisture of the soil, soil acidity and soil trophy. Most of the plants tolerates shaded and semi-shaded sites, fresh and moderately acid or nearly neutral soils of intermediate fertility. The indigenous forest species are the most valuable components of flora. Among them "Convallaria majalis", "Frangula alnus" and "Viburnum opulus" are protected by law. The parasite plant "Monotropa hypopitis" and half-parasites: "Viscum abietis", "Malampyrum nemorosum" and "Melampyrum pratense", are "botanical curiosities" of the reserve.